Synthesis of Hollow Nanofibers and Application on Detecting SF6 Decomposing Products - Lu, Zhaorui; Zhou, Qu; Wei, Zhijie; Xu, Lingna; Peng, Shudi; Zeng, Wen (Frontiers in Materials, 2019)
Hollow structured nanofibers have attracted much attention in diverse domains owing to their unique physicochemical properties and characteristics. Gas sensing is one of the most promising applications. In electrical engineering, the detection of SF6 decomposing gas products is significant to monitor the insulation status online of gas insulated switchgear (GIS). This mini-review presents the developments of hollow structured nanofibers in synthesis strategies and gas sensing application, especially in the detection of SF6 decomposing gas products, including hydrogen disulfide (H2S), sulfur dioxide (SO2), thionyl fluoride (SOF2), and sulfuryl fluoride (SO2F2). In addition, the gas sensing mechanism of metal oxide hollow nanofibers based gas sensor are discussed.